Relation of social media literacy, trust, and information quality on public communication behaviour in urban local government social media in Indonesia - Nur Atnan; Ana Nadhya Abrar (Penerbit Universiti Kebangsaan Malaysia, 2023)
The previous study and theory showed that social media literacy, trust, and quality of information influence public communication behaviour towards local government social media. Hence, this article analyses the relation among those three elements in the context of urban areas in Indonesia. This research uses a mixed method on sequential explanatory strategy, a collaboration of quantitative and qualitative methods conducted subsequently with dominancy on the quantitative methods. The authors selected 100 persons randomly and proportionally as the research sample. In addition, 12 persons from selected followers, social media specialists, academicians, and civil society. Research shows that social media literacy, trust, and quality information on local government social media are good, yet the issue is in the public communication behaviour towards governments' social media. Furthermore, 41.2% of those three elements simultaneously influence the communication behaviour. The most dominant variable influencing communication behaviour is media social literacy and people's trust, while the quality of information has no significant impact. This research is based on social media data in 2022 in three urban cities in Indonesia, namely Bandung, Semarang and Surabaya. They were chosen based on the categories that the local government uses social media for at least 10 years and has a high number of social media users.